The Theological Metaphors of Marx - Dussel, Enrique (Duke University Press, 2024)
Cover -- Contents -- Translator's Note, by Camilo Pérez-Bustillo -- Foreword: On Karl Marx's Negative Meta-Theology, by Eduardo Mendieta -- Preliminary Words, by Enrique Dussel -- Prologue to the English-Language Edition: The Criticism of Theology as the Criticism of Economics, by Enrique Dussel -- Part I: The Critique of Fetishism -- 1: Fetishism in the Young Marx, 1835-1857 -- 2: Fetishism in the Four Versions of Capital, 1857-1882 -- 3: A Critique of Capital's Fetishistic Character -- Part II: Theological "Metaphors" -- 4: Marx's "Metaphorical" Theology -- 5: The Cultic Sacrifice of the Fetish: The Use of Biblical Texts -- 6: Marx's Atheism and That of the Prophets of Israel -- Appendix: The Epistemological Decolonization of Theology -- Notes -- Index -- A -- B -- C -- D -- E -- F -- G -- H -- I -- J -- K -- L -- M -- N -- O -- P -- Q -- R -- S -- T -- U -- V -- W -- Y -- Z.